2022
DOI: 10.1097/mcc.0000000000000921
|View full text |Cite
|
Sign up to set email alerts
|

The liver-gut-axis: initiator and responder to sepsis

Abstract: Purpose of reviewThe 'gut-liver axis' is thought to play an important role in pathogenesis of sepsis. Despite a wealth of experimental data to support the concept of reciprocal crosstalk between gut and liver through bacterial translocation and shaping of the microbiome by liver-derived molecules, for example bile acids, clinical data, and in particular diagnostic and therapeutic options, are limited. Recent findingsAssessment of organ failure in the current definition of sepsis is operationalized by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Endotoxins and antigens are transported from the gut into the circulation. [20][21][22] Gut-origin sepsis is a process in which bacteria and bacteria-associated products incite a systemic response. These systemic responses are responsible for other clinical manifestations in critically ill patients with syndromes, such as acute respiratory distress syndrome (ARDS) and multiple organ dysfunction syndrome (MODS).…”
Section: Bt In Sepsismentioning
confidence: 99%
“…Endotoxins and antigens are transported from the gut into the circulation. [20][21][22] Gut-origin sepsis is a process in which bacteria and bacteria-associated products incite a systemic response. These systemic responses are responsible for other clinical manifestations in critically ill patients with syndromes, such as acute respiratory distress syndrome (ARDS) and multiple organ dysfunction syndrome (MODS).…”
Section: Bt In Sepsismentioning
confidence: 99%
“…Indeed, circulating bile acids are better predictors of sepsis-related mortality than liver function parameters, such as bilirubin [ 10 , 43 ]. Therefore, several authors speculated that bile acids play an active role in the pathogenesis of sepsis [ 10 , 29 , 45 ]. Moreover, studies have shown that HMG-CoA reductase inhibitors (drugs that significantly inhibit cholesterol and, subsequently, bile acid synthesis) reduce mortality in sepsis and infection-related ARDS [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This causes frequent transitory bacteremia and could trigger VAP. Impaired lung bacterial clearance, secondary to innate immune deficiency described in cirrhosis, could also be responsible for bacterial proliferation and subsequent VAP [ 19 ].…”
Section: Discussionmentioning
confidence: 99%